New Insights into the Mutual Promotion of Rosacea, Anxiety, and Depression from Neuroendocrine Immune Aspects - Yang X; Cai M (Dove Medical Press, 2023)
Xiaoting Yang, Mei Cai Department of Dermatology and Venereology, the Second Affiliated Hospital of Kunming Medical University, Kunming, Yunnan, 650101, People's Republic of ChinaCorrespondence: Mei Cai, Department of Dermatology and Venereology, the Second Affiliated Hospital of Kunming Medical University, No. 374, Yunnan-Myanmar Avenue, Kunming, Yunnan, 650101, People's Republic of China, Tel +86 13888532488, Email caimei5867@163.comAbstract: Rosacea is a common chronic inflammatory skin disease with a complex etiology and undefined pathogenesis, and there is still a lack of targeted clinical treatment. Patients with rosacea are at a higher risk of anxiety and depression compared to the healthy population. Compared to skin conditions such as acne and psoriasis, rosacea has been much less studied in relation to multiple-etiology psychiatric disorders such as anxiety and depression. In contrast to the mainstream belief that the causal association between rosacea and psychiatric disorders is that rosacea increases the psychological burden of patients and thus triggers psychiatric disorders simply by altering their facial appearance, this review outlines the possible common mechanisms between rosacea and anxiety and depression disorders, starting from the pathophysiological mechanisms of transient receptor potential family cation channels, HPA axis, and Th1/Th17 cell polarization. It envisages the possibility of the neuroendocrine-immune interplay between rosacea and anxiety and depression, and new ideas on the complex causal relationship between rosacea and psychiatric disorders, offering more orientations to open up new therapeutic approaches for rosacea.Keywords: rosacea, anxiety disorders, depressive disorders, neurological factors, endocrine factors, immunological factors